2014
DOI: 10.1523/jneurosci.0905-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic T-Type Ca2+Channels Modulate Dendrodendritic Mitral–Mitral and Mitral–Periglomerular Connections in Mouse Olfactory Bulb

Abstract: Mitral cells express low-voltage activated] modulates evoked release. We demonstrate that Cav3.x-mediated Ca 2ϩ influx from even one mitral cell at membrane potentials between Ϫ65 and Ϫ50 mV is sufficient to produce feedback inhibition from periglomerular neurons. Deinactivation of Cav3.x channels by hyperpolarization increases T-type Ca 2ϩ influx upon repolarization and increases feedback inhibition to produce subthreshold modulation of the mitral-periglomerular reciprocal circuit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 57 publications
1
19
0
1
Order By: Relevance
“…In this case, the mechanism depends either on spike-waveform through presynaptic Kv3.4 [29 ] or on the increase in basal calcium during subthreshold depolarization via activation of P/Q type calcium channels [30,31]. Modulation of basal calcium concentration by presynaptic membrane potential is also the main mechanism of d-ADF in auditory neurons [32,33], mitral cells of the olfactory bulb [34] and sensory neurons of the Aplysia [35]. However, in granule cells of the dentate gyrus, the mechanism of d-ADF remains unknown [18,36].…”
Section: Analog-digital Signaling In the Axonmentioning
confidence: 99%
“…In this case, the mechanism depends either on spike-waveform through presynaptic Kv3.4 [29 ] or on the increase in basal calcium during subthreshold depolarization via activation of P/Q type calcium channels [30,31]. Modulation of basal calcium concentration by presynaptic membrane potential is also the main mechanism of d-ADF in auditory neurons [32,33], mitral cells of the olfactory bulb [34] and sensory neurons of the Aplysia [35]. However, in granule cells of the dentate gyrus, the mechanism of d-ADF remains unknown [18,36].…”
Section: Analog-digital Signaling In the Axonmentioning
confidence: 99%
“…Two types of juxtaglomerular interneuron classes -periglomerular (PG) and short axon (SA) cells -are hypothesized to mediate feedforward and lateral inhibition, respectively, with differential impacts on the temporal dynamics of MTC responses (Aungst et al, 2003, Shao et al, 2009, Shirley et al, 2010, Fukunaga et al, 2012, Shao et al, 2012, Liu et al, 2013, Whitesell et al, 2013, Banerjee et al, 2015, Najac et al, 2015, Liu et al, 2016b, Geramita and Urban, 2017. Additionally, feedback inhibition mediated by reciprocal connections between MTCs to PG or SA cells may also shape MTC temporal patterning (Gire and Schoppa, 2009, Fekete et al, 2014, Najac et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…*P Ͻ 0.05, **P Յ 0.01, and ***P Յ 0.001. PSP) (Awatramani et al 2005;Fekete et al 2014;Ivanov and Calabrese 2003;Ludwar et al 2009;Shapiro et al 1980;Shu et al 2006). In previous experiments we demonstrated that B21-B8 synaptic transmission is potentiated by subthreshold depolarizations.…”
Section: Input Activation and Modulation Of B21-b8 Synaptic Transmissmentioning
confidence: 86%
“…Plasticity mediated via an alteration in the background intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) has been reported in other systems (Awatramani et al 2005;Christie et al 2011;Fekete et al 2014;Ivanov and Calabrese 2003;Shu et al 2006). An interesting feature of this type of control is its potentially graded nature.…”
mentioning
confidence: 77%
See 1 more Smart Citation